Innovative Wearable Technology for Visually Impaired - Azizan N.; Jalaluddin B.M.; Shaffie E.A.; Rahman D.H.A.; Manan M.R.; Ahmad N.I.; Abdullah A.Z. (EDP Sciences, 2025)
In Malaysia, the prevalence of blindness for all ages is 0.2%, and low vision is 2.44% (based on the National Eye Survey, 1996). Vision impairment severely impacts the quality of their lives and can contribute to social isolation and difficulty walking. Therefore, the invention of Innovative Wearable Technology for Visually Impaired People is important for helping them navigate with speed and confidence by detecting nearby obstacles using ultrasonic waves and notifying them with the speaker, MP3 player, and vibration. The preceding technology encountered several technical challenges that hindered its optimal functionality. The primary issue revolved around the use of the Arduino Uno, which proved to be prohibitively expensive and impractical for integration into a wearable device due to its cumbersome size and restricted mobility. This rendered the previous solution less feasible for assisting visually impaired individuals who require a compact and efficient navigation aid. Another significant limitation pertained to the simultaneous employment of a buzzer and a motor as outputs, leading to potential confusion for users. The concurrent activation of these outputs might have caused difficulties in interpretation and user discomfort, undermining the device's overall effectiveness in aiding visually impaired individuals during their navigation endeavors. Considering these challenges, the development of Innovative Wearable Technology for Visually Impaired People seeks to overcome these drawbacks by introducing a more cost-effective and user-friendly solution. Therefore, this paper proposes Innovative Wearable Technology for Visually Impaired People, which aims to address the shortcomings of existing aids and provide enhanced assistance to the visually impaired community. ? The Authors.